Andrographis Paniculata (Burm. F.) Nees Induces Clinical and Sputum Conversion in Pulmonary Tuberculosis Patients - Riswahyuni Widhawati; Endang Hanani; Jamal Zaini (Medicine Science, 2015)
The aim of this study was to determine whether Andrographus paniculata capsule induces clinical and sputum conversion in pulmonary tuberculosis (TB) patients. Randomized, placebo-controlled, double-blind pi¬lot study was conducted to pulmonary tuberculosis patient who admitted to Pulmonology Polyclinic of Persahabatan Central General Hospital, Jakarta. A total of 44 pulmonary TB patients were randomly divided into two groups including one group received standard antituberculosis drugs + Andrographis paniculata (n=21) (AP) and one group received standard antituberculosis drugs + placebo (n=23). APC was given 500 milligram per day for eight weeks. The distribution of sex, body weight and body mass index (BMI) as well as the frequency of cough and feature of chest radiography were not significantly different between groups (P >0.05). The proportion of posi¬tive smears in both groups decreased over time until by the twelve weeks, none remained positive. The rate of decline was more pronounced in the AP group reach statistically at weeks 4 and 6 compared to placebo group (P < 0.05). Adjunc¬tive supplementation of Andrographis paniculata (Burm. F.) Nees was to accelerated the beneficial therapeutic effect of TB chemotherapy by improving clinical and sputum response. [Med-Science 2015; 4(1.000): 1869-75]